Barb and the battle for Bailiwick - Abdo, Dan; Jason (Jason Linwood Patterson); Abdo, Dan. (New York : Simon & Schuster Books for Young Readers, 2023)
A ragtag crew of Berzerkers and five Wise Wizards with rusty powers come together to stop an evil witch from taking over their land, as Barb attempts to harness the mystical power of the Ghost Blade and lead the charge.
Ages 8-12.
Grades 4-6.
Keywords: Graphic novels; Adventure and adventurers -- Fiction; Wizards -- Fiction; Fantasy; Graphic novels